Respiratory chain complex I is related to oxidative phosphorylation in gastric cancer stem cells - Chunwei Peng; Weibiao Kang; Yunsong Li (STEMedicine, 2022)
Background: Cancer stem cells (CSCs) are the main cause of resistance to anti-cancer drug therapy and distant metastasis of tumors, including gastric cancer. The metabolism of CSCs is an important factor in the maintenance of its stemness. This study is intended to explore the role of oxidative phosphorylation in gastric CSCs.